The structure and kinematics of the ISM around HD 192281 - Arnal, Edmundo Marcelo (2011)
Aims. This work aims at investigating the interaction of HD 192281 (O5 Vn((f))p) with its local ISM. The purpose is to analyse the effects that a massive star has on the structure and kinematics of its surrounding gas. Methods. To carry out this study, we used high-resolution radio continuum and 21-cm H i line data from the Canadian Galactic Plane Survey (CGPS). This data base was complemented with radio continuum, infrared, and molecular data retrieved from available surveys. Given that HD 192281 is very likely a runaway star, we attempt to establish whether the observed H i distribution can be interpreted in terms of a simple bow shock model. Results. Analysis of the H i data shows the presence of an H i feature likely to be associated with HD 192281. This feature remains detectable from ~5 to-10 km s-1. At the most negative radial velocities, the shape of the H i feature is highly reminiscent of a bow shock structure seen projected onto the plane of the sky. This feature has counterparts at radio-continuum, infrared, and CO emissions. The analysis of the radio continuum data suggests a thermal spectrum for the gas related to this structure.